2001
DOI: 10.1046/j.1365-313x.2001.00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of blue‐light sensing in tomato using mutants deficient in cryptochrome 1 and phytochromes A, B1 and B2

Abstract: SummarySeveral novel allelic groups of tomato (Solanum lycopersicum L.) mutants with impaired photomorphogenesis have been identi®ed after g-ray mutagenesis of phyA phyB1 double-mutant seed. Recessive mutants in one allelic group are characterized by retarded hook opening, increased hypocotyl elongation and reduced hypocotyl chlorophyll content under white light (WL). These mutants showed a speci®c impairment in response to blue light (BL) resulting from lesions in the gene encoding the BL receptor cryptochrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
109
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(119 citation statements)
references
References 56 publications
(97 reference statements)
10
109
0
Order By: Relevance
“…Arabidopsis is the sole plant species for which the full set of photoreceptor genes has been characterized (Demarsy and Fankhauser 2009;Inoue et al 2010;Nagatani 2010;Chaves et al 2011). In Solanaceae, photoperception and light signaling have been mainly investigated in tomato, tobacco and potato (Perrotta et al 2000;Weller et al 2001;Fernández et al 2005;Rutitzky et al 2009). High-throughput transcriptomic analyses have demonstrated extensive sequence and functional conservation among phenotypically distinct Solanaceae species potato, tomato, pepper, petunia, tobacco and Nicotiana benthamiana, although species-specific transcripts were also indentified (Rensink et al 2005;Rutitzky et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Arabidopsis is the sole plant species for which the full set of photoreceptor genes has been characterized (Demarsy and Fankhauser 2009;Inoue et al 2010;Nagatani 2010;Chaves et al 2011). In Solanaceae, photoperception and light signaling have been mainly investigated in tomato, tobacco and potato (Perrotta et al 2000;Weller et al 2001;Fernández et al 2005;Rutitzky et al 2009). High-throughput transcriptomic analyses have demonstrated extensive sequence and functional conservation among phenotypically distinct Solanaceae species potato, tomato, pepper, petunia, tobacco and Nicotiana benthamiana, although species-specific transcripts were also indentified (Rensink et al 2005;Rutitzky et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, global gene-expression profiling in Nicotiana and Solanum species has demonstrated that light perception and signaling employ shared and exclusive pathways to control several photomorphogenic and photoperiodic responses (Rensink et al 2005;Rutitzky et al 2009). Petunia transcriptome exhibits high sequence and functional conservation to tomato transcript profiles (Rensink et al 2005) and, in this species deetiolation and anthocyanin biosynthesis are mainly controlled by phyA-and cry1-mediated signaling (Weller et al 2001). However, the overexpression of CRY2 has also led to enhanced anthocyanin accumulation in tomato fruits (Giliberto et al 2005;Lopez et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are also responsible for the so-called low fluence responses (LFR) that exhibit the classical red/ far-red photoreversible characteristic of phytochrome function. LFR are normally induced by redlight photon fluences above approximately 1 mol m Ϫ2 (Furuya and Schäfer, 1996;Whitelam and Devlin, 1997;Neff et al, 2000;Weller et al, 2001).…”
mentioning
confidence: 99%
“…Studies using phyA mutants and plants overexpressing phyA indicate that this photoreceptor is responsible for the very low fluence responses (VLFR) and for the far-red-light-dependent high-irradiance responses (HIR; Furuya and Schäfer, 1996;Whitelam and Devlin, 1997;Neff et al, 2000;Weller et al, 2001). Both responses do not show the classical red/far-red photoreversibility.…”
mentioning
confidence: 99%